Long-Term Therapy of Chronic Hepatitis B With Lamivudine - Lau, Daryl T; Farooq Khokhar, M; Doo, Edward; Ghany, Marc G; Herion, David; Park, Yoon; Kleiner, David E; Schmid, Peter; Condreay, Lynn D; Gauthier, Josée; Kuhns, Mary C; Jake Liang, T; et al. (Hepatology (Baltimore, Md.), 2000)
Lamivudine therapy induces improvements in chronic hepatitis B in a high proportion of patients, but prolonged therapy is limited by the development of viral resistance. We analyzed clinical responses and virologic resistance in 27 patients treated continuously with lamivudine for 2 to 4 years. Serum transaminases, hepatitis B virus (HBV) DNA by both branched DNA (bDNA) signal amplification and quantitative polymerase chain reaction were monitored at 4- to 8-week intervals. Virologic resistance to lamivudine was confirmed by the presence of mutations in the YMDD motif of the polymerase gene by restriction fragment-length polymorphism analysis. Serum HBV-DNA levels decreased rapidly in all treated patients, falling by 4 to 5 logs within 1 year. Transaminase levels also decreased and were normal in 70% of patients at 1 year, at which point liver histology had improved in 81% of patients. Viral resistance began to emerge after 8 months of therapy, eventually developing in 14 patients, including 76% of hepatitis B e antigen (HBeAg)-positive patients but only 10% of HBeAg-negative patients. Lamivudine withdrawal led to reappearance of wild-type HBV species, but retreatment led to more rapid reappearance of the mutant virus. Clinical, serum biochemical, and histologic improvements were maintained in the 13 patients who did not develop resistance. Thus, long-term therapy with lamivudine resulted in maintained improvements in virologic, biochemical, and histologic features of disease in most patients with HBeAg-negative chronic hepatitis B and in the subgroup of HBeAg-positive patients with high serum transaminase levels. A high rate of resistance limited efficacy, particularly in patients who remained HBeAg positive on therapy. (Hepatology 2000;32:828-834.)